A new crinipelloid species (Marasmiaceae, Agaricales) from Pakistan - Izhar, Aiman; Asif, Muhammad; Niazi, Abdul Rehman; Khalid, Abdul Nasir (Phytotaxa, 2022)
Moniliophthora pakistanica sp. nov. is described from Punjab, Pakistan, based on micro- and morphological characteristics and phylogenetic analysis. The taxon is characterized by a creamy to brownish basidiomes, a depressed or subumbonate and tomentose pileus with distinct orange to brown zones, a hairy stipe, oblong to ellipsoid basidiospores (4.7–8.5 × 4–6 μm), frequent clavate to flexuous cheilo- and pleurocystidia with apical projections, common long setiform terminal hairs in both pileipellis and stipitipellis, rhizomophs, and growth on fallen plant debris. A detailed description of macro- and microscopic characters and field photographs of collections are given. Based on our phylogenetic analysis, M. iopus is found to be a close relative of the new species. Two phylograms inferred from the datasets of nrITS and nrLSU sequences, and a comparison with phylogenetically closely related species are provided.